Quality in stroke care during the early phases of the COVID-19 pandemic: A nationwide study. (March 2023) - Blauenfeldt, Rolf A; Hedegaard, Jakob N; Kruuse, Christina; Gaist, David; Wienecke, Troels; Modrau, Boris; Damgaard, Dorte; Johnsen, Søren P; Andersen, Grethe; Simonsen, Claus Z
Introduction: Evidence-based early stroke care as reflected by fulfillment of process performance measures, is strongly related to better patient outcomes after stroke and transient ischemic attack (TIA). Detailed data on the resilience of stroke care services during the COVID-19 pandemic are limited. We aimed to examine the quality of early stroke care at Danish hospitals during the early phases of the COVID-19 pandemic. Materials and methods: We extracted data from Danish national health registries in five time periods (11 March, 2020–27 January, 2021) and compared these to a baseline pre-pandemic period (13 March, 2019–10 March, 2020). Quality of early stroke care was assessed as fulfilment of individual process performance measures and as a composite measure (opportunity-based score). Results: A total of 23, 054 patients were admitted with stroke and 8153 with a TIA diagnosis in the entire period. On a national level, the opportunity-based score (95% confidence interval [CI]) at baseline for ischemic patients was 81.1% (80.8–81.4), for intracerebral hemorrhage (ICH) 85.5% (84.3–86.6), and for TIA 96.0% (95.3–96.1). An increase of 1.1% (0.1–2.2) and 1.5% (0.3–2.7) in the opportunity-based score was observed during the first national lockdown period for AIS and TIA followed by a decline of −1.3% (−2.2 to −0.4) in the gradual reopening phase for AIS indicators. We found a significant negative association between regional incidence rates and quality-of-care in ischemic stroke patients implying that quality decreases when admission rates increase. Conclusion: The quality of acute stroke/TIA care in Denmark remained high during the early phases of the pandemic and only minor fluctuations occurred.